Hubungan Perubahan Berat Badan Ibu Selama Hamil Dengan Berat Badan Bayi Lahir Di RSUD Dr. Moewardi - SALAEH, SAREEHA; , Winarsih Nur Ambarwati,S.Kep.,NS, ETN.,M.K; , Dewi Suryandari, S.Kep.,NS (2014)
Background: Heavy increase of pregnant mother body represent the existence of mother adaptation to foetus growth, while newborn baby body weight represent the part of foetus growth result able to be influenced by heavy increase of mother body during pregnancy. This research purpose knows the correlation between heavy change of pregnant mother body during pregnancy with weight body of baby born in RSUD Dr. Moewardi. Methods: This research type is quantitative descriptive with cross sectional approach. Population used in this research is all of post partum mother birthing in RSUD Dr. Moewardi accounted 354 respondent use sample accounted 78 respondents. Sampling taking technique using accidental sampling. This research instrument use checklist. Result: From result collected by 78 respondents there are weight of less pregnancy mother body accounted by 33 persons (42.3%), appropriate responder counted 32 persons (41%) and excessive responder body weight counted 13 persons (16.7%). Weight of baby body born less counted 15 babies (19%), normallly counted 62 babies (79.5%) and more normally counted 1 baby (1.3%). The correlation increasing of pregnancy weight body mother with weight of baby body born with spearman's rho value counted 0.228 by significance level counted 0.045, thereby can conclusion that there is correlation between heavy change mother bodies during pregnancy weighing body of baby born.